COMPARATIVE STUDY OF AWARENESS LEVEL AMONG THE FARMERS OF INDIVIDUAL MILKING SYSTEM (IMS) AND COMMUNITY MILKING SYSTEM (CMS) IN KOLAR DISTRICT OF KARNATAKA - V. JAGADEESWARY, MOHANKUMAR. S, K. SATYANARAYAN and (The Journal of Research, PJTSAU, 2017)
The dairy industry has evolved through consistent efforts and application of science and echnology during pre and post independence period of India. Consequently, India has become leading milk producer in the world with 137.7 million tonnes in 2013-14. At the same time India is the second highest populated country with 1.267 billon persons in 2014. The per capita availability of milk is around 299 grams per day in 2012-13 (Basic Animal Husbandry and Fisheries Statistics, 2014) and almost its entire produce is consumed in the domestic market and the country is neither an importer nor an exporter, except in a marginal sense. (Research and Markets, 2015)